Análise postural estática e dinâmica para a obtenção de dados em avaliação clínica - Cazú, Rafael Gialorenço (Universidade Federal de São Carlos, 2021)
This research project makes use of kinematics for a study of the subject’s postural pattern, through the processing of video images and with the use of a baropodometry platform. Men and women aged between 18 and 60 years, who self-declared that they did not have joint dysfunction, pain and physical or cognitive impairment, were subject to age. The analysis obtained two postural patterns, the first non-static pattern and then a non-dynamic pattern in motion. In the static pattern, an analysis was made through the baropodometry platform that presents the pressures of loads and surfaces of the subjects’ plantar regions. In the dynamic pattern, the subject was filmed in motion, in profile and posterior positions, allowing the reconstruction of a model in three dimensions. For the analysis of the images of the videos, software was developed in C ++ language that used the libraries for image processing, ac OpenCV and 3D visualization called ac VTK. The information collected from this analysis served to compare the subject’s movements evaluated in gait, associated with the image of the pressure of the step and the plantar areas of the same subject, in order to determine patterns related to the types of steps with the analysis of the dynamic patterns. The type of foot cava and the movements of the hip on the skull-tail axis and the flexion and extension movements of the right hip were predominant in this research. Therefore, it is feasible to use the programming for the professional’s clinical reasoning, helping for a good conduct of assessment, diagnosis, orientation and monitoring of developments in the treatment of physiotherapy.
Static and dynamic postural analysis to obtain data in clinical evaluation
Keywords: Cinemática; Padrão da marcha; Processamento de imagem; Aprendizado de máquina; Kinematics; Marching pattern; Image processing; Machine learning; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL; ENGENHARIAS::ENGENHARIA ELETRICA